2023
DOI: 10.3389/fonc.2022.1023714
|View full text |Cite
|
Sign up to set email alerts
|

Look how far we have come: BREAST cancer detection education on the international stage

Abstract: The development of screening mammography over 30 years has remarkedly reduced breast cancer–associated mortality by 20%-30% through detection of small cancer lesions at early stages. Yet breast screening programmes may function differently in each nation depending on the incidence rate, national legislation, local health infrastructure and training opportunities including feedback on performance. Mammography has been the frontline breast cancer screening tool for several decades; however, it is estimated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The number of patients diagnosed with breast cancer is increasing annually [ 1 , 2 ], emphasizing the need for improved screening accuracy [ 3 , 4 ], comprehensive treatment methods, and personalized treatments [ 2 , 5 ]. However, patients with breast cancer tend to be younger than those with other cancers [ 6 , 7 ], resulting in direct burdens, such as longer treatment periods and increased costs [ 8 , 9 ], as well as indirect burdens, such as adverse event treatments [ 10 ], fertility preservation [ 11 , 12 ], and lost earnings [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients diagnosed with breast cancer is increasing annually [ 1 , 2 ], emphasizing the need for improved screening accuracy [ 3 , 4 ], comprehensive treatment methods, and personalized treatments [ 2 , 5 ]. However, patients with breast cancer tend to be younger than those with other cancers [ 6 , 7 ], resulting in direct burdens, such as longer treatment periods and increased costs [ 8 , 9 ], as well as indirect burdens, such as adverse event treatments [ 10 ], fertility preservation [ 11 , 12 ], and lost earnings [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dedicated training program with specialized tutorials instructed by breast screening experts and access to self-evaluation mammogram sets with enriched abnormal cases have been suggested to ameliorate the prevalence impact and improve the interpretation skills of local radiologists 39 . The BREAST program has been shown to be an effective training platform for Australian radiologists and radiology trainees in mammographic screening interpretation 20 , 40 , 41 and has demonstrated an improvement in radiologists’ cancer detection in real-world screening programs, 42 , 43 which strongly suggests that the adoption of this type of training could enhance Shanghai radiologists’ skills and improve health outcomes for Chinese women. This has been previously shown by our work in Vietnam, which indicated that the diagnostic performance of local radiologists in detecting small abnormal lesions, such as stellate or spiculated masses, can be increased if a proper training intervention is applied 39 …”
Section: Discussionmentioning
confidence: 99%
“…Implementing mammography screening in many countries for groups of women with an increased risk of breast cancer, that is, around the age of 50, was a breakthrough in streamlining the diagnostic process. Many studies have shown a significant decrease in the risk of breast cancer mortality after introducing mammography into medical practice [ 3 , 4 ]. However, imaging methods also have limitations.…”
Section: Introductionmentioning
confidence: 99%